2013
DOI: 10.1186/1479-5876-11-68
|View full text |Cite
|
Sign up to set email alerts
|

Screening NK-, B- and T-cell phenotype and function in patients suffering from Chronic Fatigue Syndrome

Abstract: BackgroundChronic Fatigue Syndrome (CFS) is a debilitating neuro-immune disorder of unknown etiology diagnosed by an array of clinical manifestations. Although several immunological abnormalities have been described in CFS, their heterogeneity has limited diagnostic applicability.MethodsImmunological features of CFS were screened in 22 CFS diagnosed individuals fulfilling Fukuda criteria and 30 control healthy individuals. Peripheral blood T, B and NK cell function and phenotype were analyzed by flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 64 publications
4
116
1
4
Order By: Relevance
“…However, in a longitudinal study, fatigue severity was associated with daily fluctuations of the inflammatory adipokine leptin (13). Also, many studies have found increased numbers of circulating cytotoxic CD8 + cells bearing activation antigens (8,(14)(15)(16). In addition, in a crosssectional study, Hornig et al (17) reported a distinct cytokine inflammatory signature associated with early disease.…”
mentioning
confidence: 98%
“…However, in a longitudinal study, fatigue severity was associated with daily fluctuations of the inflammatory adipokine leptin (13). Also, many studies have found increased numbers of circulating cytotoxic CD8 + cells bearing activation antigens (8,(14)(15)(16). In addition, in a crosssectional study, Hornig et al (17) reported a distinct cytokine inflammatory signature associated with early disease.…”
mentioning
confidence: 98%
“…To date recent studies have indicated abnormal elevations of Tregs in CFS/ ME patients in comparison to healthy controls [16,29]. Most of these Tregs expressed the transcription factor Foxp3.…”
Section: Discussionmentioning
confidence: 97%
“…Таким образом, в настоящее время на основа-нии экспрессии CD27, CD28, CD45RA и CD62L можно выделить следующие субпопуляции Т-лимфоцитов: фенотип «наивных» клеток мож-но описать как CD27 + [11]. Для выделения популяции лимфоцитов в периферической крови применяли моно-клональные антитела против CD45 человека, конъюгированные с флуоресцентным краси-телем Krome Orange (клон J.33, кат.…”
Section: Cd28unclassified